Adoptive Gay Father Families: Parent–Child Relationships and Children's Psychological Adjustment. Issue 2 (22nd August 2013) - Golombok, Susan; Mellish, Laura; Jennings, Sarah; Casey, Polly; Tasker, Fiona; Lamb, Michael E.
<x xml:space="preserve">Abstract</x> Findings are presented on a U.K. study of 41 gay father families, 40 lesbian mother families, and 49 heterosexual parent families with an adopted child aged 3–9 years. Standardized interview and observational and questionnaire measures of parental well‐being, quality of parent–child relationships, child adjustment, and child sex‐typed behavior were administered to parents, children, and teachers. The findings indicated more positive parental well‐being and parenting in gay father families compared to heterosexual parent families. Child externalizing problems were greater among children in heterosexual families. Family process variables, particularly parenting stress, rather than family type were found to be predictive of child externalizing problems. The findings contribute to theoretical understanding of the role of parental gender and parental sexual orientation in child development.